2015
DOI: 10.1055/s-0035-1549921
|View full text |Cite
|
Sign up to set email alerts
|

Lower Body vs. Upper Body Resistance Training and Arterial Stiffness in Young Men

Abstract: Resistance training has been shown to increase arterial stiffness. The purpose of the present study was to examine and compare the systemic arterial stiffness responses to acute lower body (LRT) and upper body (URT) resistance training. 20 healthy young men [median age: 26 years (interquartile range 23, 32)] underwent LRT, URT and whole body resistance training (WRT). Before and immediately after, as well as 20, 40 and 60 min after each training session, we measured the cardio-ankle vascular index (CAVI) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The acute effects of one bout of resistance exercise on arterial stiffness can be different based on the exercising limbs. Li et al reported that one bout of upper-limb resistance exercise increased baPWV, but lower-limb resistance exercise did not increase central artery stiffness in young men [39]. Similarly, in young adults, one bout of lower-limb resistance exercise did not show any negative effect on central artery stiffness [40].…”
Section: Discussionmentioning
confidence: 96%
“…The acute effects of one bout of resistance exercise on arterial stiffness can be different based on the exercising limbs. Li et al reported that one bout of upper-limb resistance exercise increased baPWV, but lower-limb resistance exercise did not increase central artery stiffness in young men [39]. Similarly, in young adults, one bout of lower-limb resistance exercise did not show any negative effect on central artery stiffness [40].…”
Section: Discussionmentioning
confidence: 96%
“…This automated device noted the BP and HR in both brachial and ankle locations of the supine subjects, and the procedure conformed strictly to the American Heart Association guidelines [33]. Both the left and right CAVI values were automatically calculated from an electrocardiogram (ECG), phonocardiogram, and brachial and tibial wave forms [34]. Prior to normal assessment, four standard cuffs were positioned around the left and right upper arm and ankles with ECG leads linked to the wrist and a microphone located on the mid breastbone for phonocardiography.…”
Section: Subjects and General Designmentioning
confidence: 99%
“…Prior to normal assessment, four standard cuffs were positioned around the left and right upper arm and ankles with ECG leads linked to the wrist and a microphone located on the mid breastbone for phonocardiography. Vascular length (VL) was indirectly assessed from the height of the subjects by using the following formula [34]: VL = 0.77685 × height (cm) − 1.7536. The ECG on the wrist and the phonocardiogram at the mid breastbone was used to detect the initial notch of pulse wave at the heart and ankle joint.…”
Section: Subjects and General Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many studies on measures of arterial stiffness and exercise, aimed at preventing an increase in arterial stiffness, have been reported. However, there are only a few studies that have compared the effects of exercise training arterial stiffness, as evaluated by simultaneously measured baPWV and CAVI7,8,9,10,11 ) . Li et al showed a difference in response between baPWV and CAVI after resistance training7 ) .…”
Section: Introductionmentioning
confidence: 99%